Assessing Human Trampling Effects in Alpine Vegetation: A Case Study from the Belianske Tatras - Veronika Piscová; Michal Ševčík; Andrej Sedlák; Juraj Hreško; František Petrovič (Diversity)
Although the topic of trampling of alpine vegetation has been addressed by many authors in recent years, many unanswered questions still remain. The generalization of vegetation response patterns to trampling would be valuable, especially for problematic alpine areas, which are unsuitable for large hiking loads. Such an area is the limestone Belianske Tatras, which has been closed to tourists since 1978. Only one trail has been accessible in the area since 1993 as a one-way trail, and since 2008 it has been used as an educational two-way trail. Since there is renewed discussion about making the Belianske Tatras accessible to tourists, we sought answers to the following questions: (1) regenerated communities are more resistant to trampling than the native ones; (2) individual species in different communities react to trampling in the same way; and (3) some species can disappear or become extinct after being trampled. We conducted research in the form of an experiment according to the standard Cole and Bayfield protocol. We trampled three plant communities in 2008, treating them as native, and in 2022, treating them as regenerated. The regenerated communities appeared to be more resistant, although this came at the expense of some species disappearing or becoming extinct as a delayed response. Re-opening the area could be considered.